Tree species and size diversity of Akure Strict Nature Reserve, Nigeria (2023)
Size and species structures control the natural mechanisms maintaining high structural diversity. Use of size inequality and species diversity measures singly for conservation decisions brings about inconsistent results. Therefore, most conservation efforts fail due to lack of understanding of mechanisms promoting coexistence of tree species. However, relationship between size inequality and species diversity indicates the natural mechanism promoting coexistence of high species diversity. Therefore, this study investigated the relationship between tree size inequality and species diversity in Akure Strict Nature Reserve. Eighteen and twelve plots (30m x 30m) were laid on parallel transects of 3.60km long and 50m width in Old-growth and Riparian forests, respectively. Trees with diameter-at-breast-height (dbh) ≥ 10cm were counted and identified to species level. Tree diameter at base, middle and top and total height were measured using girth tape and Relaskop. Tree species diversity (Shannon-Weiner; Simpson; Margalef indices) and dbh inequality measures (Gini coefficient, Gini; Coefficient of Variation, CV; Skewness Coefficient, Skewness) were computed and compared. Stem biomass were computed and converted to carbon stock. Data were analysed using descriptive, and correlation analysis at α0.05. Fifty-five (56) tree species representing 17 families were found in the forest. Species diversity indices were higher in Riparian while size inequalities in Old-growth forests. GC correlate with Shannon-Weiner (r=0.54; n=18, p≤0.018) and Margalef (r=0.473; n=18, p≤0.04) in Old-growth while GC correlate with CV (r=0.716; n=12, p≤0.09) in Riparian forests. The size inequality measures were strongly related with each other in Riparian while species and size inequality measures were strongly related with each other in Old-growth forests. The carbon stocks of Old-growth and Riparian forests were 117.21Mg/ha and 43.47Mg/ha, respectively. Triplochiton scleroxylon and Bridelia micrantha contained highest carbon stock in Old-growth and Riparian forests, respectively. Asymmetric mode of interaction in the absence of competition shows competition for below-ground resource, especially presence of moisture and nutrient gradient. Size inequality among different and within the same species determined coexistence tree communities in Old-growth and Riparian forests of Akure Strict Nature Reserve, respectively.